A Pattern-Based Development Approach for Interaction Flow Modeling Language - Rodriguez-Echeverria, Roberto (2020)
Rodriguez-Echeverria, R., Preciado, J. C., Rubio-Largo, Á., Conejero, J. M., & Prieto, Á. E. (2019). A Pattern-Based Development Approach for Interaction Flow Modeling Language. Scientific Programming,[7904353]. https://doi.org/10.1155/2019/7904353